Failure analysis of the piston used in a pneumatic down the hole impactor. Issue 1 (1st December 2022) - Pan, Peng; Li, Yongsheng; Chen, Yunbo; Wang, Jinnan; Zuo, Lingli; Chen, Rongrong; Zhang, Baoyan
Abstract : In this paper, the failure mechanism of the piston in the pneumatic down the hole (DTH) impactor has been studied. Failed piston microstructure has been analyzed using the light optical microscopy (OM) and scanning electron microscope (SEM). Impact toughness test and the Rockwell hardness test were conducted. Results showed the following: a) The carburizing layer of IQCT failed piston is mainly composed of acicular martensite and lower bainite after the carburizing-tempering-isothermal quenching-cryogenic treatment-tempering (IQCT), and there are collapses on the impact side and outer surface of the piston, mainly fatigue failure. b) IQT failed piston samples are subject to carburizing-tempering-isothermal quenching-tempering treatment (IQT). The carburized layer is mainly composed of high-carbon martensite, carbide and retained austenite. The transition layer is still composed of lower bainite and acicular martensite, but the volume fraction of lower bainite increases significantly and the core is mainly composed of lower bainite. It has the best impact toughness, up to 61.5 J/cm 2, which is mainly fatigue failure. c) OQT failed piston sample is subject to carburizing-tempering-oil quenching-tempering (OQT). The carburized layer is mainly composed of acicular martensite, the transition layer is composed of acicular martensite (AM) and lath martensite (LM), and the core is mainly composed of LM. The impact toughness of the sample is the worst. Therefore, fatigue fracture failure is caused.